2011
DOI: 10.1103/physrevd.83.124008
|View full text |Cite
|
Sign up to set email alerts
|

Binary neutron star mergers: Dependence on the nuclear equation of state

Abstract: We perform a numerical-relativity simulation for the merger of binary neutron stars with 6 nucleartheory-based equations of state (EOSs) described by piecewise polytropes. Our purpose is to explore the dependence of the dynamical behavior of the binary neutron star merger and resulting gravitational waveforms on the EOS of the supernuclear-density matter. The numerical results show that the merger process and the first outcome are classified into three types; (i) a black hole is promptly formed, (ii) a short-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
422
5
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(449 citation statements)
references
References 52 publications
19
422
5
3
Order By: Relevance
“…General relativistic simulations of BNS systems have found that only a small amount of mass is unbound by the merger (M ej ¼ 10 À4 M -10 À2 M ) [19], while Newtonian smoothed particle hydrodynamics simulations have more optimistic predictions (M ej * 10 À2 M ) [20]. BHNS systems have more asymmetric mass ratios, and are thus generally more favorable for the ejection of neutronrich material during the disruption of the neutron star.…”
Section: Introductionmentioning
confidence: 99%
“…General relativistic simulations of BNS systems have found that only a small amount of mass is unbound by the merger (M ej ¼ 10 À4 M -10 À2 M ) [19], while Newtonian smoothed particle hydrodynamics simulations have more optimistic predictions (M ej * 10 À2 M ) [20]. BHNS systems have more asymmetric mass ratios, and are thus generally more favorable for the ejection of neutronrich material during the disruption of the neutron star.…”
Section: Introductionmentioning
confidence: 99%
“…Although the total mass of the system exceeds the maximum mass of the static spherically symmetric NS, the merger remnant does not necessarily collapse into a black hole immediately. This is because the maximum mass is increased by ∆M ∼ several 10 % by the thermal and rotational effects [30]. If the total mass of NS-NS is larger than this effective critical mass, a black hole is immediately formed and the amplitude of GW decays rapidly.…”
Section: Overview Of Evolution Of Ns-ns and Gw From Itmentioning
confidence: 99%
“…Hotokezaka et al [17] shows that there are three types of post-merger behaviour of binary neutron stars, namely prompt formation of black hole, formation of short-lived hyper-massive neutron star and formation of long-lived hyper-massive neutron star. There is a distinct amplitude peak at the spectrum of the gravitational-wave waveform of the post-merger stage.…”
Section: Constraining the Nuclear Equation Of State Through The Post-mentioning
confidence: 99%